Penerapan Data Mining Menggunakan Algoritma Fp-Growth Untuk Menganalisa Pola Penjualan Obat (Studi Kasus : Klinik Anissa) - Muhtajuddin Danny; Syaiful Umam (DPPM Universitas Pelita Bangsa, 2022)
Anissa Clinic is a health service located in South Cikarang. At Anissa Clinic, there are many sales and purchases of drugs. Transaction data will continue to grow every day and in the pharmacy the sales transaction data is only stored as an archive or bookkeeping and it is not known what the benefits of these data are. For this reason, it is necessary to do an analysis using data mining to generate information in increasing sales at Anissa Clinic. The purpose of this study is to determine consumer buying patterns by looking for linkages of items that come out together, with the data mining method used in this study is the association rule method. Association is one of the data mining techniques from the Fp-Growth algorithm which functions to find relationships between products in consumer shopping carts. Keywords: Anissa Clinic, Data Mining, Association Rules, Fp-Growth Algorithm.